OsRPK1, a novel leucine-rich repeat receptor-like kinase, negatively regulates polar auxin transport and root development in rice - Zou, Yu; Liu, Xiaoyu; Wang, Qing; Chen, Yu; Liu, Cheng; Qiu, Yang; Zhang, Wei (Biochimica et biophysica acta, 2014)
Leucine-rich-repeat receptor-like kinases (LRR-RLKs) represent the largest subfamily of putative RLKs in plants. Although several members in this subfamily have been identified, the studies about the relationships between LRR-RLKs and root development are still few. We previously identified a novel LRR-RLK in rice roots, and named it OsRPK1. In this study, we first detected OsRPK1 kinase activity in vitro, and assessed its expression profile. We then investigated its biological function using transgenic rice plants over- and under-expressing OsRPK1. The OsRPK1 gene, which encodes a Ca(2+)-independent Ser/Thr kinase, was predominantly expressed in root tips, leaf blades, and undifferentiated suspension cells, and was markedly induced by treatment with auxin or ABA. Knockdown of OsRPK1 promoted the growth of transgenic rice plants, and increased plant height and tiller numbers. In contrast, over-expressing plants showed undeveloped adventitious roots, lateral roots, and a reduced root apical meristem. OsRPK1 over-expression also inhibited the expression of most auxin efflux carrier OsPIN genes, which was accompanied by changes in PAT and endogenous free IAA distribution in the leaves and roots. The data indicated that OsRPK1, a novel leucine-rich-repeat receptor-like kinase, affects the root system architecture by negatively regulating polar auxin transport in rice. This study demonstrated a common regulatory pathway of root system development in higher plants, which might be initiated by external stimuli via upstream receptor-like kinases and downstream carriers for polar auxin transport.